Adubação nitrogenada em cultura energética – cártamo - Balena, Fernando Luiz da Cruz (2020)
Efficient crop nutrient management plays an important role in the well-being of communities worldwide, supporting the production of food, feed, biomass, and alternative fuels that depend on viable and sustainable agriculture. The objective of this study was to evaluate the effects of nitrogen fertilizer application on the direct and indirect productive components of safflower. Sowing was carried out under field conditions on a small rural property in the municipality of Toledo, PR, Brazil. The treatments were arranged in randomized blocks with four replicates, and consisted of five doses of nitrogen (0, 50, 100, 150, and 200 kg ha-1 ) in the form of urea (45% N), which was manually incorporated into the soil 30 days after plant emergence. Morphometric parameters were evaluated at the full flowering stage, and the yield and chemical composition of the achenes were assessed during physiological maturation of the plants. Data were analyzed using analysis of variance (ANOVA) at the 5% significance level. Regression equations were fitted to the means of the quantitative variables. For grain yield, protein content, and lipid and fiber data, a linear correlation was applied. The results showed that safflower grain yield was strongly influenced by the application of N-urea, with the maximum yield at a dose of 120 kg ha-1 N. At this level of use, grain production was around 520 kg ha-1 . A joint analysis of the regression equation for N-urea application and grain yield, and the prices of N and safflower grains used, revealed that the most economical dose was 70 kg ha-1 , which provided the maximum profit per unit area. There was a positive linear correlation between grain yield and protein content (r = 0.51). However, there was no statistically significant correlation between grain yield and oil content and/or fiber content. Stem diameter, aerial dry biomass, grain yield, number of branches, and floral chapters per plant increased with N fertilization application, indicating that safflower culture responds positively to nitrogen fertilization. We conclude that sustainable use of nitrogen fertilizer using the maximum economic efficiency dose, can contribute to better plant health and, at the same time, reduce production costs.